Engels et l'émancipation des femmes - Europe Solidaire Sans Frontières - Trat, Josette (Engels et savants révolutionnaires, 1997)
Keywords: 1800-1899; 1900-1909; 1900-1999; 1970-1979; approches et analyses; capitalisme; classe ouvrière; corps; cours; discipline; europe; famille; france; justice sociale; marxisme; premier cycle; périodes historiques; russie; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques; travail

America's working women: A documentary history, 1600 to the present - Baxandall, Rosalyn Fraad, (1939- ...).; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

The Women’s Art Society of Montreal: A Century of Commitment to the Arts - Holowach-Amiot, Elaine (Musée McCord d'histoire canadienne, 1994)
The Women's Arts Society of Montreal was founded in 1894 by Mary Martha Phillips and Mrs. James H. Peck (nee Mary Alice Skelton). The parent body of the Society (The Women's Art Association of Canada) was incorporated in Toronto in 1892. The goal of the Montreal Society was to integrate women into the art world at a time in history when women had few rights and were relegated to other roles. In 1907, the Montreal branch of the Women's Art Association of Canada broke away from the Toronto organization to form their own independent society. During and after the First World War, the Women's Arts Society of Montreal focussed on philanthropic efforts, assisting disabled and convalescing veterans and their families. After 1938, the Society’s efforts shifted towards entertainment and other branches of the arts, such as theatre, music and studio art. In the late 1990s the Society began to accept men as members.
Keywords: 1800-1899; 1900-1999; amériques; discipline; groupes de femmes; histoire; histoire des femmes*; montréal; périodes historiques; régions géographiques; sciences humaines; sofia; thématiques; travail

La création musicale des femmes au Québec - Lefebvre, Marie-Thérèse (De mémoire de femmes, 1991)
Connues principalement comme pédagogues et interprètes, les femmes en musique ont mis du temps à se faire reconnaître dans le domaine de la composition. C’est ce volet encore ignoré de notre histoire que La Création musicale des femmes au Québec nous fait découvrir, depuis l’apport des communautés religieuses en Nouvelle-France jusqu’aux expérimentations électroacoustiques des vingt dernières années, du phénomène culturel de la musique de salon au début du siècle aux performances multimédias de nos contemporaines…
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; DIG; amériques; arts; biographie; discipline; femmes* artistes; femmes* compositrices; musique; périodes historiques; québec; régions géographiques; thématiques; travail

Les femmes au tournant du siècle 1880-1940 : âges de la vie, maternité et quotidien - Institut québécois de recherche sur la culture., Denise; Lemieux (Institut québécois de recherche sur la culture,, 1989)
Keywords: 1800-1899; 1880-1889; 1890-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; histoire et politique; inégalités; maternité; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; soc2264; sociologie; systèmes d'oppressions; thématiques; travail

The social origins of private life: A history of American families, 1600-1900 - Coontz, Stephanie (Haymarket series, 1988)
Current debates about the future of the family are often based on serious misconceptions about its past. Arguing that there is no biologically mandated or universally functional family form, Stephanie Coontz traces the complexity and variety of family arrangements in American history, from Native American kin groups to the emergence of the dominant middle-class family ideal in the 1890s. Surveying and synthesizing a vast range of previous scholarship, as well as engaging more particular studies of family life from the seventeenth to the nineteenth centuries, Coontz offers a highly original account of the shifting structure and function of American families. Her account challenges standard interpretations of the early hegemony of middle-class privacy and “affective individualism,” pointing to the rich tradition of alternative family behaviors among various ethnic and socioeconomic groups in America, and arguing that even middle-class families went through several transformations in the course of the nineteenth centure. The present dominant family form, grounded in close interpersonal relations and premised on domestic consumption of mass-produced household goods has arisen, Coontz argues, from a long and complex series of changing political and economic conjunctures, as well as from the destruction or incorporation of several alternative family systems. A clear conception of American capitalism’s combined and uneven development is therefore essential if we are to understand the history of the family as a key social and economic unit. Lucid and detailed, The Social Origins of Private Life is likely to become the standard history of its subject.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; division of household labor; division sexuelle du travail; famille; féminisme matérialiste; his4443; histoire; histoire et politique; premier cycle; périodes historiques; rapports de classe; rapports sociaux de sexe; régions géographiques; sciences humaines; sociologie; sociologie de la famille; thématiques; travail; travail domestique; états-unis

Cheap amusements: Working women and leisure in turn-of-the-century New York - Peiss, Kathy Lee (Temple University Press, 1986)
Contenu: The Homosocial World of Working-Class Amusements -- Leisure and Labor -- Putting on Style -- Dance Madness -- The Coney Island Excursion -- Cheap Theater and the Nickel Dumps -- Reforming Working Women's Recreation.
Keywords: 1800-1899; 1900-1999; approches et analyses; cours; discipline; his4443; histoire; histoire des femmes*; histoire et politique; loisirs des femmes*; new york; premier cycle; périodes historiques; rapports sociaux de sexe; sciences humaines; sociologie; thématiques; travail; travail des femmes*

Capitalisme, Patriarcat et ségrégation professionnelle des sexes - Hartmann, Heidi; Coryell, Rosette (Questions Féministes, 1978)
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amérique du nord; amériques; angleterre; approches et analyses; capitalisme; corps; cours; discipline; europe; france; féminisme matérialiste; histoire et politique; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; soc1016; sociologie; systèmes d'oppressions; thématiques; travail; états-unis